Sun and moon compasses in Tylos europaeus (Crustacea Isopoda). Issue 3 (4th May 2018) - Ciofini, Alice; Ugolini, Alberto
Abstract : Experiments conducted in the 1950s provided first evidences that both the sun and the moon constitute astronomical compass cues in the zonal recovery of the supralittoral isopod Tylos europaeus . Whereas the sun-based orientation of this species has been thoroughly confirmed, no other investigation on its ability to orientate according to the moon has been carried out. In our studies we tested adult individuals in a confined environment and demonstrated that: (1) animals can rely on the moon as a compass orienting factor despite the difficulties met in the time-compensated use of this celestial body; (2) the lunar orientation is largely independent of the geomagnetic field; and (3) the moon compass seems to operate throughout the 24-hr period thus even in the absence of the direct vision of the moon. Moreover, our preliminary tests conducted to assess the existence of discrete time-keepers regulating the sun and the moon compasses pointed out a partial separation between the two mechanisms even though further investigations are required to clarify this aspect.